Etograma de mico-leão-preto (Leontopithecus chrysopygus, Mikan, 1823) em cativeiro, com ênfase no comportamento reprodutivo - Oliveira, Mayara Ferreira de (2016)
The interest in knowing and observing animals increased the habit of keeping them in captivity, starting the creation of zoos around the world. They have being modernized through the time and acquiring a new concept in education and research, in which the conservation of the species is placed in the foreground. The research in captivity cover many areas of study, such as parasitology, pathology, genetics, and more, allowing closer contact with the animal and making it easier to access the information that is difficult to get in nature. However, the study of animal behavior stands out among these areas, as it collaborates with several researches, allowing a more detailed knowledge about the behavioral characteristics of the species, as described in this study. Populations of black lions tamarins (Leontopithecus chrysopygus) kept in captivity are targets of researches that aim to get more information about the species, helping their conservation. The preparation of a detailed behavioral catalog for the species was the objective of this article, emphasizing the description and analysis of reproductive and socio-reproductive behavior. Took part in the first stage of the study four couples of captive black lions tamarins in an extra section of the São Paulo Zoo. In the second stage, there were more four captives couples from the Conservation Center of Wild Fauna of the State of São Paulo (CECFAU), where two of them also belonged to the previous group. The observations lasted four months in each study area and were held from Ad libitum methods to make the ethogram (90 full observation hours) and focal animal with instant registration, with 30-minute sessions and 1-minute intervals for frequency analysis. It was also analyzed the use of the grounds of the using area (divided into quadrants) and the proximity of the animals, which have resulted in a high frequency of use of the upper quadrants in the sections of the Sao Paulo Zoo, as well as the holding area and plays in facilities of the CECFAU, being noticed, in both areas, the animals away from each other most of the time of the observation. Forty-five different behavioral acts were detected, divided into 11 behavioral categories to make the analysis of the frequencies easier. The categories most performed by the animals were Locomotion, Food and Physiological behavior for couples of the Sao Paulo Zoo, as well as for couples CECFAU, except for the category “Not visible” that showed high representativeness for this latter individuals, corroborating the frequency that the animals stay in holding area and burrows, where they were out of the observer's reach. In Reproductive and Socio-reproductive behaviors were observed "copulation", "smell genital”, "hold behind", "copulation simulation" and "genital markings". It is suggested non-invasive endocrine studies, by analyzing fecal metabolites concentrations that, associated with observations of behavior, can certainly help the reproductive study of the species.